Biosynthesis of zinc oxide nanoparticles by using fruits extracts of Ananas comosus and its antibacterial activity - Raja Ahmad, Raja Adibah; Harun, Zawati; Othman, Mohd Hafiz Dzarfan; Basri, Hatijah; Yunos, Muhamad Zaini; Ahmad, Azlinnorazia; Mohd Akhair, Siti Hajar; Abd Rashid, Abdul Qaiyyum; Azhar, Faiz Hafeez; Alias, Siti Salwa; Ainuddin, Ainun Rahmahwati (Penerbit UTM Press, 2019)
Biosynthesis of metallic nanoparticles using plants, enzymes, and microorganism has been known as eco-friendly alternative compared to other conventional physical and chemical methods. Recently, the biological synthesis of nanoparticles has been a keen interest among researchers and scientists due to its simple technique, eco-friendliness, non-toxic and low in cost. Thus, in this current work, the synthesis of zinc oxide nanoparticles (ZnO-NPs) using reduction agent from fruit extracts of Ananas Comosus was reported. The biosynthesized ZnO-NPs were characterized using Field Emission Scanning Electron Microscope (FESEM) paired with Energy Dispersive X-ray analysis (EDX), UV-Vis absorption spectroscopy and X-ray diffraction (XRD). The average size of the nanoparticles was found to be in the range of 30-57nm. The antibacterial activity of ZnO-NPs was performed via agar diffusion method against pathogenic organisms. It was observed that the biosynthesized ZnO-NPs in the process has the efficient antibacterial performance against Escherichia coli (E-coli). In conclusion, the green synthesized ZnO-NPs using the fruit extract of Ananas Comosus was successfully conducted and interestingly it has also been proved to exhibit antibacterial effect against E. coli strains.